A facile strategy for rapid in situ synthesis of Cu2O on PP non-woven fabric with durable antibacterial activities. (October 2022) - Gong, Junyao; Fu, Zhuan; Zhou, Sijie; Zhang, Chunhua; Zhu, Na; Wang, Xiaofeng; Zhou, Zhaozixuan; Liu, Xin; Xia, Liangjun; Xu, Weilin
Abstract: As the commercially filter material used in a face mask, polypropylene (PP) non-woven fabric is considerably important for personal and medical protection, which plays an essential role in reducing exposure to infectious respiratory bacteria and airborne aerosol particles. Herein, a facial and rapid strategy for in situ synthesis of cuprous oxide nanoparticles (Cu2 O NPs) on PP nonwovens with the durable antibacterial property was demonstrated using high-temperature polydimethylsiloxane based on the concept of material engineering. Owing to the instantaneously slight melting of the PP surface layer at high temperature, Cu2 O NPs were rapidly in situ constructed and immobilized on the fiber surface to form an organic and inorganic hybrid layer. The as-prepared Cu2 O-PP non-woven fabric exhibited excellent broad-spectrum antibacterial properties towards both the Gram-positive and Gram-negative bacteria, showing an inhibition zone of 39 mm and 18 mm for B. subtilis and P. aeruginosa, respectively. Furthermore, a durable antibacterial property was also achieved after 50 times of standard washing. Finally, the as-prepared Cu2 O-PP non-woven fabric was used as an insert filter to fabricate a four-layer PP-based face mask, which may significantly improve the antibacterial performance of masks. The method provides a facile engineering strategy for medical protection with great application potential. Graphical abstract: Image 1 Highlights: A novel strategy for rapid synthesis of Cu2 O NPs on PP fabric was proposed. Cu2 O NPs were constructed on slight melting surface layer of PP fiber within 50s. Cu2 O-PP exhibited durable antibacterial properties in protection applications.